Mechanical Behaviour Of Carbon Reinforced Polymer Using RTM And VIP Techniques For Aircraft Spoiler Hinge - Abdullah, Zailinda (2019)
The existing hinge bracket for aircraft spoilers is mostly made of metallic materials. The change of the materials of the hinge bracket from metallic to composites can contribute to a low weight structure. The demand for fibre-reinforced plastic (FRP) composites in aircraft industries especially the hinge bracket for spoilers is increasing over the years. However, the current fabrication process for aircraft hinge brackets used as spoilers incurred high costs in terms of tooling, production, and testing cost. Therefore, in this thesis, flat panel with different number and orientation of woven carbon fibre layers in laminated composites system were used to determine its mechanical behaviour. Two different processes have been used, namely Resin Transfer Moulding Process (RTM) and Vacuum Infusion Process (VIP). The fabrication processes were used to fabricate FRP composite with different plies as parameters. The parameters used were 8, 16, 24 and 32 plies of woven carbon fibres. Besides that, the orientation of the carbon fibre remains constant which are [0/90]n and [45/-45]n. For the mechanical test, these FRP composites undergo tensile tests and flexural tests. From the experiment, it is shown that 8CF/EP composites fabricated using VIP have 10.6 % higher in specific strength obtained from the tensile test and 64.4 % higher in specific strength obtained from the flexural test. It is also indicated that the composites with 8 plies of carbon FRP composite fabricated by using VIP gave good tensile and flexural strength compared to the composites fabricated by using the RTM method. Moreover, 8 plies of carbon FRP gave better mechanical properties compared to other different plies of carbon FRP composite. A comparison of mechanical properties between FRP composites made by VIP with existing hinge for aircraft spoiler shows that the UTS of FRP composites is 58% lower than existing material; AA7075-T651.